DIMENSI CORPORATE ENTREPRENEURSHIP DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN - Mulyanto, Kukuh (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2013)
This research examine the effects of corporate entrepeneurship onfirm performance.Corporate entrepreneurship includes dimensions,among others: innovation, risk taking, aggressiveness in competition,autonomy and proactivity. In the research indicated that corporateentrepeneurship has an influence on company performance.Summarysaid that corporate entrepeneurship is positively effected to firmperformance.